O Desenvolvimento Da Teoria Da Vontade No Pensamento De Santo Agostinho Em De Diversis Quaestionibus Ad Simplicianum - Jordao, Thiago Paulino [UNIFESP] (2018)
On Augustine"S Shoulders Rests A Philosophical Production Stigmatized Both By The Free Will Of The Human Volition And By The Efficacy Of Divine Grace. Aware Of The Tension Between These Two Movements, The Author Himself Identifies, Among His Writings, A Work In Which He Considered To Have Duly Solved This Question: De Diversis Quaestionibus Ad Simplicianum. The Present Research Will Investigate The First Book Of This Treatise To Simplician, Comparing It With The Previous And Later Writings, To Analyze The New Moment That The Text Represents In The Augustinian Theory Of The Will. From It, The Human Will Is Described By Augustine As Incapable Of Moving In Search Of Divine Help, Thus Being At The Mercy Of The Initiative Of Grace To Desire The Good. In View Of This New Understanding Of The Author, The Following Problematic Will Be Addressed: Does Augustine Still Preserve Any Value To The Human Will In De Diversis Quaestionibus Ad Simplicianum? The Hypothesis Developed In This Work Is That, Despite The Protagonism